Síntese de Fischer-Tropsch sobre perovskitas LayCu0,4Fe0,6O3 - Souza, José Roberto de (2010)
The current natural gas production of 52 Mm3d-1 and the large projects for its expansion has been setting new boundaries for the Brazilian industry of oil and gas. So far, one of the biggest challenges regards to the logistics for gas transportation from offshore fields. Therefore, the transformation of natural gas into gasoline, diesel and/or olefins via Fischer-Tropsch synthesis would be an alternative to this matter. In this work, the production of hydrocarbons by Fischer-Tropsch synthesis in a slurry reactor was investigated and a perovskite-type catalyst (LayCu0,4Fe0,6O3 ± d) was used with y varying from 0 to 1 on a molar basis. In addition, Nb2O5 support was also applied in order to observe the selectivity of the produced hydrocarbons by the Fischer-Tropsch process. It is shown that the hydrogen conversion was influenced by the support as well as the different phases of the samples. The kinetic results for the CO2 production suffered great influence with the introduction of the Nb2O5 support throughout the series of samples studied. The catalysts allowed obtaining welldefined cuts of hydrocarbons in the range of C1-C6 and C17-C28, and these results were clearly influenced by the support and the lanthanum content. The higher olefin/paraffin ratio obtained was 1.8 when using a non-supported perovskite with y equal to 0.8. This would indicate the suitability of using this material for the production of olefins